Pengaruh Pemberdayaan Karyawan dan Stress Kerja Terhadap Kepuasan Kerja Karyawan - Styawahyuni, Ari; Yuniari, Made (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
The study aimed to determine the effect of employee empowerment and work stress simultaneously on employee job satisfaction, and to determine the effect of empowerment and work stress partially on employee job satisfaction. The research was conducted on each employee in the division Kampoeng Seafood. Population of as many 49 employees Kampoeng seafood, using saturated sampling in determining the data samples and collected through observation, interviews and questionnaires. Multiple linear regression is used as a data analysis technique. Based on the results of the study found that employee empowerment and work stress simultaneously significant effect on employee job satisfaction. Employee empowerment is partially positive and significant effect on employee job satisfaction, job stress variables partially negative and significant effect on employee job satisfaction. Keywords : employee empowerment , job stress , job satisfaction Normal 0 false false false IN X-NONE X-NONE
Keywords: employee empowerment , job stress , job satisfaction